2019
DOI: 10.1038/s41598-019-52416-x
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene analysis and its use for kinase expression profiling in Fasciola hepatica

Abstract: The liver fluke Fasciola hepatica causes fasciolosis, a foodborne zoonosis affecting humans and livestock worldwide. A reliable quantification of gene expression in all parasite life stages relevant for targeting by anthelmintics in the mammalian host is fundamental. The aim of this study was to define a set of stably expressed reference genes for qRT-PCR in Fasciola studies. We determined the expression stabilities of eight candidate reference genes by the algorithms NormFinder, geNorm, BestKeeper, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Before testing kinase inhibitors, we first determined the transcript (expression) levels of potentially druggable kinases in two relevant pathologic life stages of F. hepatica: early immature flukes (here 4 weeks age) that typically cause acute fascioliasis while migrating through liver parenchyma and the adult flukes (here 12 weeks old) residing in the bile duct during chronic fasciolosis. We focused on two kinases that were previously discussed as promising anthelminthic targets against other types of parasitic flatworms such as schistosomes (7,8,19,20,(38)(39)(40)(41), and for which we previously described putative orthologs in F. hepatica (18). These were the PLK1 ortholog Fhplk1 and the ABL-TK ortholog Fhabl1 (for accession numbers, see Supplementary Table 1).…”
Section: Transcriptional Expression Of Selected Kinases In Pathogenicmentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing kinase inhibitors, we first determined the transcript (expression) levels of potentially druggable kinases in two relevant pathologic life stages of F. hepatica: early immature flukes (here 4 weeks age) that typically cause acute fascioliasis while migrating through liver parenchyma and the adult flukes (here 12 weeks old) residing in the bile duct during chronic fasciolosis. We focused on two kinases that were previously discussed as promising anthelminthic targets against other types of parasitic flatworms such as schistosomes (7,8,19,20,(38)(39)(40)(41), and for which we previously described putative orthologs in F. hepatica (18). These were the PLK1 ortholog Fhplk1 and the ABL-TK ortholog Fhabl1 (for accession numbers, see Supplementary Table 1).…”
Section: Transcriptional Expression Of Selected Kinases In Pathogenicmentioning
confidence: 99%
“…Biochemical studies confirmed that schistosomal ABL-TK and PLK1 are targets for imatinib and BI2536, respectively ( 22 24 ). We previously identified potential orthologs of ABL-TK and PLK1 kinases in F. hepatica ( 18 ), which makes imatinib and BI2536 excellent candidates for a pilot study of kinase inhibitors with fasciolicidal potential.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies confirmed that schistosomal ABL-TK and PLK1 are targets for imatinib and BI2536, respectively (22)(23)(24). We previously identified potential orthologs of ABL-TK and PLK1 kinases in F. hepatica (18), which makes imatinib and BI2536 excellent candidates for a pilot study of kinase inhibitors with fasciolicidal potential.…”
Section: Introductionmentioning
confidence: 79%
“…All qRT-PCRs were run with three technical replicates and mostly comprised three to five biological replicates. The expression of genes of interest was determined by relative quantification against the geometric mean of two reference genes (glutamylprolyl-tRNA synthetase, Fheprs, and tubulin-specific chaperone D, Fhtbcd) (18). Relative expression levels were expressed as n-fold difference vs. the expression in control flukes based on the Ct method (relative expression = 2 − Ct ).…”
Section: Mtt Assaymentioning
confidence: 99%
“…To move kinases more into the spotlight of Fasciola drug research, we recently demonstrated a cross-stage expression pattern of several kinases that have been described as anthelminthic targets in other species (18). Targeting several fluke stages by the same kinase inhibitor thus appears achievable.…”
Section: Introductionmentioning
confidence: 99%